Transcriptomic Analysis Reveals Wound Healing of Morus alba Root Extract by Up‐Regulating Keratin Filament and CXCL12/CXCR4 Signaling. (25th May 2015) - Kim, Kang‐Hoon; Chung, Won‐Seok; Kim, Yoomi; Kim, Ki‐Suk; Lee, In‐Seung; Park, Ji Young; Jeong, Hyeon‐Soo; Na, Yun‐Cheol; Lee, Chang‐Hun; Jang, Hyeung‐Jin
<x xml:space="preserve">Abstract</x> Facilitation of the wound healing process is important because a prolonged wound site increases pain and the risk of infection. In oriental medicine, an extract of Morus alba root (MA) has usually been prescribed as traditional treatment for accelerating wound healing, and it has been proven to be safe for centuries. To study the molecular mechanism of MA‐mediated skin wound healing, we performed a primary cell culture and a skin explant culture and observed significant difference between the groups with and without MA extract. In the cellular system, a real‐time cell analysis and real‐time quantitative PCR were performed. It was found that MA extract enhanced proliferation in a dose‐dependent manner on Kera‐308 cell line, and up‐regulated keratin expression including wound‐induced Krt6a. In skin explant culture, the mRNA level derived from cell outgrowth displayed a tendency toward more up‐regulated mRNA associated keratin filaments and toward a more up‐regulated mRNA level of C‐X‐C motif chemokine 12 (CXCL12) and a chemokine receptor 4 (CXCR4) axis signaling pathway downstream. In this process, we concluded that MA extract had a scientific possibility of wound repair by increasing intracellular and extracellular supports and by inducing a CXCL12/CXCR4 signaling pathway. Copyright © 2015 John Wiley & Sons, Ltd.